Islamic Constitutionalism: Social Movement and the Framework of the Indonesian Constitution - Muzayyin Ahyar; Ni’matul Huda (The Constitutional Court of the Republic of Indonesia, 2021)
The main purpose of this article is to discuss Islamic constitutionalism in the context of Indonesian social movements. Constitutionalism is part of the study of constitutional law when the discussion focuses on the concept of limiting the power of the government. Using historical and sociological approaches, this article examines socio-political circumstances in Muslim society and their relationship to the spirit of constitutionalism in Indonesia. Indonesia does not explicitly name any particular religion in its Constitution, even though most of its population is Muslim. After a series of constitutional reforms over 1999– 2002, there was no formalization of Islam in the Constitution. Two important academic questions arise when dealing with this phenomenon. First, to what extent are Indonesia’s religious social movements involved in constructing the narrative of constitutionalism? Second, how do the spirit of constitutionalism and Islam play a role in strengthening Indonesia’s Constitution? This article notes that some Muslims in Indonesia have been striving to build a narrative of Islamic constitutionalism through social movements since the nation’s pre- independence era. Nevertheless, this Islamic constitutionalism has not resulted in the formalization of an Islamic constitution in Indonesia due to several factors: the historical roots of the nation’s establishment, the pluralist stance of Indonesia’s mainstream civil Islamic movements, and the presence of the Pancasila as the state ideology. This article also reveals that Indonesia’s Muslim majority and religious authorities play a role in building the spirit of constitutionalism; however, the formalization of a specific religion as the basis of the constitution has never been realized in Indonesia.